Design and Implementation of IoT Based Smart Energy Monitor at POLNEP Informatics Engineering Laboratory - Wibowo, Fitri; Suheri, Suheri; Bibi, Sarah (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2023)
Pontianak State Polytechnic (POLNEP) Informatics Engineering Laboratory currently does not have a system that can be used to monitor the use of electrical energy. This causes the use of electrical energy tends not to be monitored properly. In an effort to implement a smart laboratory at the POLNEP Informatics Engineering Laboratory, a system is needed that can sense data related to the use of electrical energy. The purpose of this research is to provide an Internet of Things (IoT) based system that can be used to monitor and control the use of electrical energy in the POLNEP Informatics Engineering Laboratory. In addition, the system is also expected to be able to provide notifications via mobile devices to technicians and laboratory heads when detecting anomalies in voltage, current, or changes in relay status. The methodology used in this research is to use a product development approach consisting of software and hardware in a project. Broadly speaking, the steps to be carried out are: (1) Defining project goals; (2) Define project requirements based on project goals; (3) Designing system architecture; (4) Define User Experience (UX) flow; (5) Identify the parts/stages of development; (6) Assemble hardware and create program code for each section/stage; (7) Integrate each part/stage; and (8) Testing and troubleshooting.